Rational Design of Advanced Triboelectric Materials for Energy Harvesting and Emerging Applications. Issue 2 (23rd December 2022) - Duan, Qingshan; Peng, Weiqing; He, Juanxia; Zhang, Zhijun; Wu, Zecheng; Zhang, Ye; Wang, Shuangfei; Nie, Shuangxi
Abstract: The properties of materials play a significant role in triboelectric nanogenerators (TENGs). Advanced triboelectric materials for TENGs have attracted tremendous attention because of their superior advantages (e.g., high specific surface area, high porosity, and customizable macrostructure). These advanced materials can be extensively applied in numerous fields, including energy harvester, wearable electronics, filtration, and self‐powered sensors. Hence, designing triboelectric materials as advanced functional materials is important for the development of TENGs. Herein, the structural modification methods based on electrospinning to improve the triboelectric properties and the latest research progress in this kind of TENGs are systematically summarized. Preparation methods and design trends of nanofibers, microspheres, hierarchical structures, and doping nanomaterials are highlighted. The factors influencing the formation and properties of triboelectric materials are considered. Furthermore, the latest progress on the applications of TENGs is systematically elaborated. Finally, the challenges in the development of triboelectric materials are discussed, thereby guiding researchers in the large‐scale application of TENGs. Abstract : Diverse design strategies based on the structural characteristics of electrospun triboelectric materials. One method is to prepare nanofibers with different orientations including random and oriented nanofibers. Another method is to create microspheres with rough surfaces such as spherality and honeycomb. The last is to develop a hierarchical structure, e.g. porous and core–shell nanofibers.